Waste management plan with reduce, reuse, recycle (3r) method - Tika Luthfi Mahartin (Journal of Sustainability, Society, and Eco-Welfare, 2023)
Garbage is a problem that is quite concerning in Indonesia. Most of the waste generated comes from household waste and plastic waste. The increase in waste production is influenced by population growth, the speed of development and the socio-economic level of the community which grows every year. The increase in the amount of waste is not proportional to the expansion of the landfill area. Disposal/TPA conditions in several areas are already overloaded, one of which is in Batang Regency. The Randukuning TPA in Batang Regency is already overloaded with the amount of waste produced reaching 500 tons per day with a landfill area of 2.5 hectares. Waste management is a structured, comprehensive and sustainable activity that includes waste reduction and handling. One effort that can be done to reduce waste is to sort waste from its source and apply 3R (Reduce, Reuse, Recycle).